2012
DOI: 10.1044/1058-0360(2011/11-0002)
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Emergent Literacy: Efficacy of a Model That Partners Speech-Language Pathologists and Educators

Abstract: These findings suggest that professional development provided by a speech-language pathologist can yield short-term changes in the facilitation of emergent literacy skills in early childhood settings. Future research is needed to determine the impact of this program on the children's long-term development of conventional literacy skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 73 publications
2
50
0
8
Order By: Relevance
“…Finally, the three studies implementing curriculumbased language and literacy programs in preschools (Girolametto et al, 2012;Justice et al, 2010;Wilcox et al, 2011) reported positive results. For the two studies implementing a general use program for all children either over 30 weeks with 11 experimental (n ¼ 66) and 9 business-as-usual (n ¼ 72) classes (Justice et al) or with 10 trained (39 children) and 10 untrained (37 children) educators in workshops (4), class visits (3), and video feedback (Girolametto et al), significantly higher language and emergent literacy skills on standardized (Justice et al) or rating measures (Girolametto et al) were found for experimental compared to control groups.…”
Section: Slp-educator Classroom Collaboration: Evidence and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the three studies implementing curriculumbased language and literacy programs in preschools (Girolametto et al, 2012;Justice et al, 2010;Wilcox et al, 2011) reported positive results. For the two studies implementing a general use program for all children either over 30 weeks with 11 experimental (n ¼ 66) and 9 business-as-usual (n ¼ 72) classes (Justice et al) or with 10 trained (39 children) and 10 untrained (37 children) educators in workshops (4), class visits (3), and video feedback (Girolametto et al), significantly higher language and emergent literacy skills on standardized (Justice et al) or rating measures (Girolametto et al) were found for experimental compared to control groups.…”
Section: Slp-educator Classroom Collaboration: Evidence and Discussionmentioning
confidence: 99%
“…A total of 8 studies were found reporting curriculum level SLP-educator partnerships aimed at enriching language models and improving access to the curriculum through language (see Table 1). Of these, 4 involved SLP-educator classroom collaborations for elementary school children (Bland & Prelock, 1996;Kaufman, Prelock, Weiler, Creaghead, & Donnelly, 1994;Drew, 1998;Farber & Klein, 1998), 1 involved SLP-educator consultative services for secondary school students (Starling et al, 2012), and 3 involved SLP-educator consultative services for preschool children (Girolametto et al, 2012;Justice et al, 2010;Wilcox et al, 2011). All of the studies compared experimental and control groups except one (Drew), but only 2 incorporated full randomization with either a balanced (Girolametto et al) or unbalanced design (Wilcox).…”
Section: Slp-educator Classroom Collaboration: Evidence and Discussionmentioning
confidence: 99%
“…Current initial letter and letter-sound instruction includes teaching children to a) name letters, b) complete auditory tasks, listening for discrete sounds within a spoken word (phonemic awareness), and c) use pictures to learn letter-sounds [29]- [31]. These instructional strategies do not embody the print-to-sound process of decoding.…”
Section: The Problem Statementmentioning
confidence: 99%
“…Esta constatação é bastante feliz já que a leitura pode realmente cumprir não apenas uma, mas muitas funções nas vidas das pessoas e essa exposição nos primeiros anos de vida escolar pode favorecer grandemente o desenvolvimento do hábito de leitura nas diferentes situações cotidianas. Porém, uma linha de investigação interessante seria buscar acompanhar as leituras e contações realizadas por professores ao longo de um ano escolar e verificar se realmente estão alcançando todos os objetivos, no sentido sugerido por Girolametto, Weitzman e Greenberg 15 . Parte dos participantes tanto da rede municipal quanto da rede particular de ensino relataram que seus conhecimentos sobre aquisição e desenvolvimento da linguagem é bom, outra parte descreveu como regular.…”
Section: Conclusãounclassified
“…Girolametto, Weitzman e Grenberg 15 afirmaram que existem várias habilidades, adquiridas antes da exposição a um método formal de alfabetização, que preparam crianças pequenas para a aquisição de leitura e escrita proficiente. (conceitos sobre texto escrito, consciência narrativa, consciência fonológica, vocabulário e linguagem oral).…”
unclassified